Practical Asymmetries of Racial Reference - Whitehead, Kevin A; Lerner, Gene H (My University, 2013)
This report contributes to the study of racial discourse by examining some of the practical asymmetries that obtain between different categories of racial membership as they are actually employed in talk-in-interaction. In particular, we identify three interactional environments in which the ordinarily “invisible” racial category “white” is employed overtly, and we describe the mechanisms through which this can occur. These mechanisms include 1) “white” surfacing “just in time” as an account for action, 2) the occurrence of referential ambiguities with respect to race occasioning repairs that result in overt references to “white,” and 3) the operation of a recipient design consideration that we term “descriptive adequacy.” These findings demonstrate some ways in which the mundane invisibility of whiteness – or indeed, other locally invisible racial categories – can be both exposed and disturbed as a result of ordinary interactional processes, revealing the importance of the generic machinery of talk-in-interaction for understanding both the reproduction of and resistance to the racial dynamics of everyday life.
When Are Persons “White”?
Keywords: Race; Racial categories; Whiteness; Membership categorization devices; Conversation analysis